AT1 Receptor Mediated Hypertensive Response to Ang II in the Nucleus Tractus Solitarii of Normotensive Rats Involves NO Dependent Local GABA Release - Légat, Laura; Smolders, Ilse; Dupont, Alain G. (Frontiers in Pharmacology, 2019)
Aim: It is well established that angiotensin II exerts a dampening effect on the baroreflex within the nucleus tractus solitarii, the principal brainstem site for termination of baroreceptor afferents and which is densely populated with gamma-aminobutyric acid (GABA)ergic neurons and nerve terminals. The present study was designed to investigate whether local release of GABA is involved in the effects mediated by local angiotensin II within the nucleus tractus solitarii. Methods: In vivo microdialysis was used for measurement of extracellular glutamate and GABA levels and for infusion of angiotensin II within the nucleus tractus solitarii of conscious normotensive Wistar rats. The mean arterial pressure and heart rate response to local infusion of angiotensin II were subsequently monitored with a pressure transducer under anaesthesia. The angiotensin II type 1 receptor (AT1R) antagonist, candesartan, was used to assess whether responses were AT1R dependent and the nitric oxide synthase inhibitor, N(ω)-nitro-L-arginine methyl ester (L-NAME), was used to assess the involvement of nitric oxide in the evoked responses by infusion of angiotensin II. Results: Local infusion into the nucleus tractus solitarii of angiotensin II induced a significant to 9-fold increase in extracellular GABA levels; mean arterial pressure was increased by 15 mmHg. These responses were both abolished by co-infusion of either candesartan or L-NAME, demonstrating that the effect is not only AT1R dependent but also nitric oxide dependent.The pressor response to angiotensin II was reversed by co-infusion with the GABAA receptor antagonist, bicuculline. Local blockade of nitric oxide synthase decreased both, GABA and glutamate concentrations. Conclusion: Our results suggest that the AT1R mediated hypertensive response to angiotensin II within the nucleus tractus solitarii in normotensive rats is GABA and nitric oxide dependent. Nitric oxide produced within the nucleus tractus solitarii tonically potentiates local GABA and glutamate release.